Potret Identitas Marginal dalam Sastra Kontemporer: Pelabelan terhadap Anak PKI dalam Novel Namaku Alam Karya Leila S. Chudori - Ruddin, Moh.; Tabarok, Moh.; Oktaviani, Santi; Ambarwati, Ari (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the labeling process in Leila S. Chudori’s novel Namaku Alam (My Name is Alam) related to the main character’s status as a child of the Indonesian Communist Party (PKI), deviance, and its impact, using Howard S. Becker’s labeling theory. The method used is qualitative with a sociology of literary texts (soteksas) approach. Data were obtained through library research and in-depth reading, with the researcher as the main instrument. The unit of analysis includes linguistic and contextual elements that represent the labeling process. The analysis was carried out through the stages of label identification, narrative interpretation, application of Becker’s theory (stigma construction, articulation of deviation, and identity response), and connection with the social context. The results show that the character Alam received stigmatic labels such as "bastard child," "traitor," and "itchy widow child" from various social actors, such as teachers, friends, and family. The accumulation of these labels forms a deviant identity, causes psychological stress, and encourages deviant behavior, such as laziness and violence. The impact is seen in the hampered education due to the "clean environment" program and the failure of romantic relationships due to political stigma. These findings suggest that labeling in literary texts reflects social mechanisms that coercively shape identities and limit individual mobility in society.